Tingkat Kerawanan Pangan Rumah Tangga di Provinsi Nusa Tenggara Timur Tahun 2024 - Alidra, Celvin Keyla; Suhartini, Atik Mar'atis (Politeknik Statistika STIS, 2025)
Food insecurity occurs when the most basic human need, which is food, is not fullfiled, making someone difficult to carry out daily activities. The highest SDGs indicator 2.1.2 (prevalence of population with moderate or severe food insecurity based on the Food Insecurity Experience Scale (FIES)) in 2023 is in East Nusa Tenggara Province (NTT). This study aims to identify the general status of household food insecurity and analyze the influence and determine the tendency of socioeconomic access factors on the level of household food insecurity using data from the National Socio-Economic Survey (Susenas) in March 2024 using by Partial Proportional Odds Model (PPOM) of ordinal logistic regression. The results show that households living in rural areas, with a large number of household members, female household heads, older household heads, household heads with education below high school, households in the agricultural sector, unsafe drinking water, and a food expenditure share above 60 percent are more likely to experience food insecurity.